Geochemistry and U–Pb zircon dating of the Toudaoqiao blueschists in the Great Xing’an Range, northeast China, and tectonic implications - Zhou, Jian-Bo; Wang, Bin; Wilde, Simon A.; Zhao, Guo-Chun; Cao, Jia-Lin; Zheng, Chang-Qing; Zeng, Wei-Shun (Journal of Asian earth sciences, 2015)
•Toudaoqiao blueschists were metamorphosed up to HP epidote–blueschist facies.•Blueschists have OIB and N-MORB affinities.•Timing of HP metamorphism at 490–510Ma.•Toudaoqiao–Xinlin fault is the suture between the Erguna and Xing’an blocks. The Toudaoqiao Complex is a sequence of high-pressure metamorphic rocks located along the suture zone that separates the Xing’an and Erguna blocks in northeast China. The rocks were metamorphosed up to epidote–blueschist facies at P–T conditions of approximately 0.9–1.1GPa and 320–450°C. Lithological associations and major and trace element compositions indicate that the blueschists are metabasalts with ocean island basalt (OIB) and normal mid-ocean ridge basalt (N-MORB) affinities, similar to those of the Philippines intraoceanic accretionary complex formed by subduction of oceanic crust. Magmatic zircons extracted from two samples of the epidote–blueschist facies metabasalts from the North Mountain in the Toudaoqiao Complex exhibit 206Pb/238U ages of 511±5 and 516±17Ma, whereas a greenschist from the South Mountain has a 206Pb/238U age of 511±2Ma; These data show that the protoliths of the Toudaoqiao Complex are of early Paleozoic age. In addition, a granitic dike from the South Mountain exhibits a weighted mean 206Pb/238U age of 492±1Ma. These ages constrain the timing of high-pressure metamorphism in the Toudaoqiao Complex to 490–510Ma. The new data support the view that the suture zone between the Xing’an and Erguna blocks is the Toudaoqiao–Xinlin Fault, rather than the Derbugan Fault as previously thought. This suture, which extends from Xinlin, through Toudaoqiao, and southern Mongolia, named the ‘South Mongolia–Toudaoqiao–Xinlin Suture Zone’, may be an important boundary between the Central Mongolia–Erguna and Xing’an blocks.